A novel and actual mode for study of soil degradation and transportation of difenoconazole in a mango field. Issue 16 (26th February 2018) - Zhao, Fangfang; Liu, Jingkun; Xie, Defang; Lv, Daizhu; Luo, Jinhui
Abstract : Actual data for assessing the potential threat from the environmental behaviors of the difenoconazole to the ecosystem in mango field could be provided by the novel experimental design. Abstract : To supply actual data for assessing the potential threat from difenoconazole to the ecosystem, its practical environmental behaviors in a mango field were investigated through a novel mode. After optimization, a UPLC-MS/MS determination method with good accuracy and stability was developed that could be used for the residue determination. Difenoconazole residue was in situ sampled, and its degradation and transportation activity, which reflected the actual transfer characteristics in the natural environment, were researched. The results showed that the half-life of difenoconazole in the soil was 15.4 days, which may be accumulated in a year-round agricultural production system. The residue was detected in the rain settled underground, which showed that the residue transported gradually with the rainfall in vertical and horizontal directions. The results showed that difenoconazole would transport with the rainfall, although the process was slow. All the data showed that the soil ecosystem, and probably also the aquatic ecosystem, would be affected by difenoconazole residue.